Distribution of Internet Filtering Policy Information in UUM - Shane, Adel Abed Ulhure A. (2009)
This study proposes a design and implementation of Distribution of Internet Filtering Policy Information in UUM. It explains the system model, and demonstrates how to use various programming tools to know the student/staff which web-site allowed or disallowed about the block list of system and system have to any suggest from student/staff for allowed for them to using before this time block and this for some time after that repeated the administer to block for this element of block list dependent security for system, and system another part demo for administer for view and change any interface of system dependent which is system need to security and publisher the information about block list, category and policy and he have all permission to update or delete or insert all interface of system t. Web server Apech and SQL 2005 that can used to retrieved the web page when it send from database. A requirement analysis of interactive web-base for publisher any rule from system UUM to student/staff to security. Authorized user can update, delete or insert only view for system from the web page. An analysis of the technique and solution that can be put to use and decide on which solution security suitable for our system. We are testing the demo from the offer all web-site prevent from the system UUM which agree or disagree of student/staff to implement this project and take the percentage for the developer the system to achievement the security for system.